Building midwifery educator capacity in teaching in low and lower-middle income countries. A review of the literature. (February 2016) - West, Florence; Homer, Caroline; Dawson, Angela
Abstract: Aim and objective: midwifery educators play a critical role in strengthening the midwifery workforce in low and lower-middle income countries (LMIC) to ensure that women receive quality midwifery care. However, the most effective approach to building midwifery educator capacity is not always clear. This paper will explore approaches used to build midwifery educator capacity in LMIC and identify evidence to inform improved outcomes for midwifery education. Design: a structured search of bibliographic electronic databases (CINAHL, OVID, MEDLINE, PubMed) and the search engine Google Scholar was performed. It was decided to also review peer reviewed research, grey literature and descriptive papers. Papers were included in the review if they were written in English, published between 2000 and 2014 and addressed building knowledge and/or skills in teaching and/or clinical practice in midwifery educators who work in training institutions in LMIC. The Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) was used to guide the reporting process. The quality of papers was appraised in discussion with all authors. The findings sections of the research papers were analysed to identify successful elements of capacity building approaches. Findings: eighteen (six research and 12 discursive) papers were identified as related to the topic, meeting the inclusion criteria and of sufficient quality. The findings were themed according to the key approaches used to build capacity for midwifery education. These approaches are: skill and knowledge updates associated with curriculum review, involvement in leadership, management and research training and, participation in a community of practice within regions to share resources. Key conclusions: the study provides evidence to support the benefits of building capacity for midwifery educators. Multilevel approaches that engaged individuals and institutions in building capacity alongside an enabling environment for midwifery educators are needed but more research specific to midwifery is required. Implications for practice: these findings provide insight into strategies that can be used by individuals, faculties and institutions providing development assistance to build midwifery educator capacity in LMIC. Highlights: Literature review explored approaches to building midwifery educator capacity. Evidence of knowledge and skill development associated with curriculum review. Leadership and management training increased educator׳s access to resources. Collaboration built supportive relationships and enabled shared teaching resources. No single framework exists for how to build midwifery educator capacity in LMIC.